COMMERCIAL SEX WORKER COMPLIANCE WITH USING CONDOMS IN THE LOCALIZATION OF MANGROVE BAY, BATAM CITY - Rosyadi Aziz Rahmat; Devy Lestari Nurul Aulia (Universitas Batam, 2020)
Background : According to the World Health Organization (WHO) HIV continues to be a global public health problem, claiming more than 70 million people are infected with the HIV virus and around 35 million people have died. In 2015, approximately 1.1 (940 000-1300000) million people have died due to being infected with the HIV virus. There were an estimated 36.7 (34.0-39.8) million people living with HIV at the end of 2016. Globally, Sub-Saharan Africa is the most affected region, with nearly 1 in 25 adults living with HIV. (WHO 2016). The purpose of this study was to determine the compliance of commercial sex workers on using condoms in the localization of Teluk Bakau, Batam City. Method : This study used a descriptive research design. The location of this research was carried out in the localization of Teluk Bakau, Batam City. The population in this study were all commercial sex workers (CSWs) in the Teluk Bakau brothels with a total of 95 people. The sample is an object under study and is considered to represent the entire population, here the writer uses a purposive technique, namely by means of sampling based on criteria. The measuring instrument in this study using a questionnaire. This analysis was carried out on each variable. These results are in the form of distribution and percentage of each variable. Data analysis was carried out in a univariate manner by looking at the results of the frequency calculation and the presentation of the results which could later be used as benchmarks for discussion and conclusions. Results and conclusions : It can be seen that the compliance of CSWs using condoms in the Bakau Bay brothel, Batam City is the majority of the majority behave obediently as many as 46 respondents (93.9%)